USING INFORMATION GAP ACTIVITIES TO IMPROVE THE SPEAKING SKILL OF THE SECOND GRADE STUDENTS OF SMPN 13 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This classroom action research was aimed to know whether information gap activities can improve the students’ speaking skill of the second grade class VIII-4 of SMPN 13 Pekanbaru. This research was done in for times-treatments in one cycle. Thirty nine students were participated in this study. The data were collected from several sources; students’ speaking score, observation sheets, and field notes. The result showed that the mean score of post-test (71.8) was higher than mean score of pre-test (36). The observation result also showed that the there was an increase number of students’ participation in every single activity. We can see that there was an increasing average number from beingin the pre-test 80% and become 100%. It means that more than all of the students were active in teaching and learning process. It can be conclude that information gap activities can improve the students’ speaking skill of the second grade class VIII-4 of SMPN 13 Pekanbaru.Keywords: Speaking Skill, Information Gap Activities